2009
DOI: 10.1136/jnnp.2007.142786
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal diffusion tensor imaging study in symptomatic Huntington's disease

Abstract: It appears that microstructural changes influence cognitive status in HD. Although MD was significantly higher in HD compared with controls at both time points, there were no longitudinal changes in either group. This finding does not rule out the possibility that MD could be a sensitive biomarker for detecting early change in preclinical HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 30 publications
(45 reference statements)
4
41
0
Order By: Relevance
“…Abnormalities in WM microstructure have been reported in postmortem studies of humans with HD (de la Monte et al 1988;Halliday et al 1998). This research was confirmed by in vivo studies with magnetic resonance imaging (MRI), which reported extensive WM volume loss (Aylward et al 1998, 2012Thieben et al 2002;Rosas et al 2003;Fennema-Notestine et al 2004;Beglinger et al 2005;Ciarmiello et al 2006;Paulsen et al 2006;Jech et al 2007;Squitieri et al 2009;Tabrizi et al 2009Tabrizi et al , 2011Tabrizi et al , 2012Tabrizi et al , 2013) and changes in WM microstructure (Mascalchi et al 2004;Reading et al 2005;Rosas et al 2006;Bartzokis et al 2007;Sritharan et al 2010;Stoffers et al 2010;Dumas et al 2012;Matsui et al 2014). Nevertheless, these previous macro-and microstructural studies focused on wholebrain WM or Region of Interest analyses.…”
Section: Introductionmentioning
confidence: 54%
“…Abnormalities in WM microstructure have been reported in postmortem studies of humans with HD (de la Monte et al 1988;Halliday et al 1998). This research was confirmed by in vivo studies with magnetic resonance imaging (MRI), which reported extensive WM volume loss (Aylward et al 1998, 2012Thieben et al 2002;Rosas et al 2003;Fennema-Notestine et al 2004;Beglinger et al 2005;Ciarmiello et al 2006;Paulsen et al 2006;Jech et al 2007;Squitieri et al 2009;Tabrizi et al 2009Tabrizi et al , 2011Tabrizi et al , 2012Tabrizi et al , 2013) and changes in WM microstructure (Mascalchi et al 2004;Reading et al 2005;Rosas et al 2006;Bartzokis et al 2007;Sritharan et al 2010;Stoffers et al 2010;Dumas et al 2012;Matsui et al 2014). Nevertheless, these previous macro-and microstructural studies focused on wholebrain WM or Region of Interest analyses.…”
Section: Introductionmentioning
confidence: 54%
“…Previous studies have primarily relied on scalar maps (e.g., FA) derived from the diffusion tensor to perform independent registrations to a standard template (Weaver et al, 2009), and have generally failed to differentiate longitudinal changes in HD from controls (Sritharan et al, 2010;Weaver et al, 2009). Registration of DTI data using full tensor information improves both specificity and precision for detecting longitudinal changes compared to standard scalar approaches (Keihaninejad et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Although prior studies have suggested that DTI measurement is a valuable bio-marker to assess HD severity in human, limited longitudinal study has been performed to evaluate progressive changes 2531 . In this study, DTI was performed on HD monkeys and age-matched control monkeys starting at six-months and at every 6-months interval up to 48 months of age to assess changes in the integrity of the white matter across development.…”
Section: Introductionmentioning
confidence: 99%